2021
DOI: 10.3390/ma14051218
|View full text |Cite
|
Sign up to set email alerts
|

The Sclerometrical, Mechanical, and Wear Behavior of Mg-Y-Nd Magnesium Alloy after Deep Cryogenic Treatment Combined with Heat Treatment

Abstract: The paper investigates changes in the structure, microhardness, and sclerometrical and tribological properties of a Mg-Y-Nd alloy under the influence of deep cryogenic treatment (DCT) in combination with heat treatment. The solution treatment was carried out at 545 °C for 8 h, aging was carried out at 250 °C for 24 h, and the deep cryogenic treatment applied at different treatment stages was performed at −196 °C. Tests showed a significant increase in the number of β-phase precipitates identified as Mg46.1Y6.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…The above results corroborate that increasing the amount of β -phase lamellar precipitates by introducing deep cryogenic treatment to the precipitation hardening process effectively reduces the tribological wear of the investigated alloy. Similar observations can be found in the literature in works on magnesium alloys with aluminium [ 16 , 21 ] and gadolinium [ 22 , 23 , 24 , 25 , 26 ] additions, and in our previous papers concerning WE54 magnesium alloy [ 27 , 28 ].…”
Section: Research Results and Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The above results corroborate that increasing the amount of β -phase lamellar precipitates by introducing deep cryogenic treatment to the precipitation hardening process effectively reduces the tribological wear of the investigated alloy. Similar observations can be found in the literature in works on magnesium alloys with aluminium [ 16 , 21 ] and gadolinium [ 22 , 23 , 24 , 25 , 26 ] additions, and in our previous papers concerning WE54 magnesium alloy [ 27 , 28 ].…”
Section: Research Results and Discussionsupporting
confidence: 90%
“…The sub-zero treatment alone, in turn, resulted in an approximate 5–8% increase in micromechanical properties. The observed effects are the result of changes in the structure of the Mg-Y-Nd alloy studied by the authors in previous articles [ 27 , 28 ], where it was shown that deep cryogenic treatment caused a twofold increase in the number of β -phase precipitates and decrease in the grain area compared to the alloy aged without sub-zero treatment. The large number of additional precipitates formed as a result of deep cryogenic treatment after solution treatment can be explained by the formation of additional nucleation sites in magnesium alloys [ 15 ], which also occurs, among others, in magnesium alloys with aluminum and with gadolinium [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 33 , 34 ].…”
Section: Research Results and Discussionmentioning
confidence: 88%
See 3 more Smart Citations